PSYCHOLOGICAL WELL-BEING: FAMILY AND FAITH COMMUNITY AS AGENT OF MICROSYSTEM - Anwar, Moh. Khoerul (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2023)
Psychological well-being plays an important role in families and faith communities as agents of the microsystem in ecological counseling. This study aims to explore the related families’ well-being and faith communities. This article explores a variety of issues related to youth, parenting, and extremism; parenting trends in the millennial era; theories of change towards the well-being of families and faith communities; and psychological well-being based on families and faith communities as microsystem agents. Some of these things show that the well-being of families and faith communities affects the life of the community.   Keywords: psychological well-being, parenting, family, faith community